Seasonal distribution of human-to-human pathogens in airborne PM2.5 and their potential high-risk ARGs - Zuo, Zhiwei; Pan, Yuanyuan; Huang, Xueyun; Yuan, Tao; Liu, Cheng; Cai, Xihong; Xu, Zhongji (Frontiers in Microbiology, 2024)
Airborne microorganisms, an emerging global health threat, have attracted extensive studies. However, few attentions have been paid to the seasonal distribution of airborne pathogens, in particular their associations with antibiotic resistance genes (ARGs). To this end, two-week daily PM2.5 samples were consecutively collected from Nanchang in four seasons, and the human-to-human pathogens were screened based on high-throughput sequencing. The results showed that there were 20 pathogenic taxa in PM2.5 in Nanchang, and the highest relative abundance of pathogens was observed in winter (5.84%), followed by summer (3.51%), autumn (2.66%), and spring (1.80%).Although more than half of pathogenic taxa were shared by the four seasons, the analysis of similarities showed that pathogenic community was shaped by season (r=0.16, p<0.01). Co-occurrence network analysis disclosed significant interactions among pathogens in each season. Moreover, some dominant pathogens such as Plesiomonas shigelloides, Bacteroides fragilis, and Escherichia-Shigella were hub pathogens. In addition, PICRUSt2 predicted that there were 35 high-risk ARG subtypes in PM2.5, and the pathogens had strongly positive correlations with these ARGs. Even some pathogens like Plesiomonas shigelloides, Bacteroides fragilis, Aeromonas, Citrobacter, may be multi-drug resistant pathogens, including beta-lactam, aminoglycosides, chloramphenicol and multi-drug resistances, etc. Both air pollutants and meteorological conditions contributed to the seasonal variation of airborne pathogenic bacteria (r= 0.15, p<0.01), especially CO, O3, PM2.5, temperature and relative humidity. This study furthers our understanding of airborne pathogens and highlights their associations with ARGs.